Synthesis, structure activity relationship, radiolabeling and preclinical evaluation of high affinity ligands for the ion channel of the N-methyl-d-aspartate receptor as potential imaging probes for positron emission tomography. Issue 5 (1st March 2015) - Klein, Pieter J.; Christiaans, Johannes A.M.; Metaxas, Athanasios; Schuit, Robert C.; Lammertsma, Adriaan A.; van Berckel, Bart N.M.; Windhorst, Albert D.
Graphical abstract: Abstract: The N -methyl-d -aspartate receptor (NMDAr) is involved in many neurological and psychiatric disorders including Alzheimer's disease and schizophrenia. Currently, it is not possible to assess NMDAr availability in vivo. The purpose of this study was to develop a positron emission tomography (PET) ligand for the NMDAr ion channel. A series of di- and tri- N -substituted diarylguanidines was synthesized. In addition, in vitro binding affinity for the NMDAr ion channel in rat forebrain membrane fractions was assessed. Compounds10, 11 and32 were radiolabeled with either carbon-11 or fluorine-18. Ligands [ 11 C]10 and [ 18 F]32 were evaluated ex vivo in B6C3 mice. Biodistribution studies showed higher uptake of [ 11 C]10 and [ 18 F]32 in forebrain regions compared with cerebellum. In addition, for [ 11 C]10 54% and for [ 18 F]32 70% of activity in the brain at 60 min was due to intact tracer. Pre-treatment with MK-801 (0.6 mg·kg −1, ip) slightly decreased uptake in NMDAr-specific regions for [ 18 F]32, but not for [ 11 C]10 . As such [ 18 F]32 has the best characteristics as a PET tracer for the ion channel of the NMDAr.